LEGALIZAÇÃO DE AGROTÓXICOS NO BRASIL: CRISE AXIOLÓGICA CONTEMPORÂNEA E EXAME DAS REPERCUSSÕES SOBRE OS DIREITOS HUMANOS - LEYCE OLIVEIRA SANTOS (2024)
SANTOS, Leyce Oliveira. Legalization of agrotoxins in Brazil: contemporary axiological crisis and examination of the repercussions on Human Rights. 132 fls. Dissertação (Mestrado em Direito) – Faculdade de Direito, Universidade Federal de Mato Grosso do Sul, 2024. Given that the human species has always acted in the controversial duality of being the main agent of environmental degradation, as well as its primary preserver, legislative permissiveness towards pesticides represents the formalization of an imminent risk to the environment and current and future generations. Since the dawn of agriculture, when it was established for the cultivation of consumable species, the need arose to control other invasive or predatory species known as pests. However, it was only after World War II that society began to normalize an industry of chemicals presented as a solution for pest control, also proposing an increase in production, seed protection, and greater durability of agricultural products. With the legislative changes regarding agrotoxins, the problem of this study is to analyze whether the new legislation is consistent with the reaffirmation of human rights and the promotion of sustainable development adopted by the Brazilian state in the international scenario. The aim is to examine the provisions of the new legislation compared to the old law, identifying positive and negative points of the change, from the perspective of building a sustainable future and maintaining human rights for future generations. The thematic delimitation is related to the historically constructed and contemporary Brazilian panorama, in which previous incentives for the purchase and use of agrotoxins, combined with the recent amendment to the agrotoxins law in Brazil, are within the same scenario as the Sustainable Development Goals established in the 2030 Agenda. The research is justified as there is abundant scientific evidence of the risks of agrotoxins use, while a widespread culture persists that agriculture without chemicals is currently unfeasible. The methodology used will be hypothetical-deductive, where the established hypothesis is that the harmful potential of agrotoxins in nature and human health is being underestimated in legislative action, failing to apply the precautionary principle adequately at the time of normative elaboration, which may harm consolidated human rights and SDG’s agreed upon in the 2030 Agenda. The multidisciplinary consultation will be conducted through bibliographic and documentary research, based on the paradigm of extended anthropocentrism conceived by Ingo Wolfgang Sarlet and Tiago Fensterseifer, with a theoretical evaluative approach and emphasis on sociocritical analysis. The conclusion is that the precautionary principle was not adequately applied at the time of the elaboration of Law No. 14.785/2023, as gaps, unconstitutionalities, and unconventionalities that violate the protection of human rights and the fulfillment of agreed SDGs are identified. KEYWORDS: Human Rights. Environmental Law. Agrotoxins. Risks. Precautionary principle. New Agrotoxins Law (nº 14.785/2023).